Oral Health Conditions and Physical Performance in Two Different Professional Team Sports in Germany: A Cross-Sectional Study - René Schwesig; Paulina Born; Eduard Kurz; Stephan Schulze; Matti Panian; Robert Percy Marshall; Thomas Bartels; Andreas Wienke; Christian Ralf Gernhardt (Sports)
Background: Oral health (OH) has been linked to overall health status and common physical performance (PP). Aim: The objective was to compare the OH and PP of two third league professional team players from different sports (soccer, ice hockey). Methods: Twenty-nine professional soccer players (mean ± standard deviation; age: 24.3 ± 4.1 years) and twenty-one ice hockey players (age: 27.7 ± 3.6 years) were investigated regarding several dental scores (DMFT, PSI, API, PBI) by one calibrated examiner. The PP diagnostic includes measurement of grip strength as well as postural stability and regulation using posturography. Results: Concerning dental scores, relevant sport-specific differences for PSI (1 vs. 2; p < 0.001), API (29 vs. 48; p = 0.001), and PBI (14 vs. 42; p < 0.001) in favor of soccer players were found. Ice hockey players reported significantly more tension of the temporomandibular joint (p = 0.004) and showed lower readiness for regular check-ups (p < 0.001) and additional oral hygiene (p = 0.045). In contrast, ice hockey players were more balanced and displayed a higher level of weight distribution (p < 0.001), especially in the anterior-posterior direction (p = 0.002). Conclusions: Based on more intensive oral hygiene and dental care, the investigated professional soccer players showed partially better OH conditions compared to the ice hockey players examined. In summary, the OH and PP results reflect the different sport-specific requirements and related training impacts on athletes.